2013
DOI: 10.1080/00207543.2013.774491
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of remanufacturing scheduling

Abstract: This article systematically organises and reviews peer-reviewed journals up to July 2011 to access progress in the scheduling of remanufacturing operations. The simple (infinite capacity, no part commonality, and deterministic parameters), single product remanufacturing scheduling problem is solved using reverse material requirements planning. Material requirements planning and performance-based objectives of the 1990s were replaced by cost-based integer programming models that can achieve solutions to size-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…The existing literature review studies in remanufacturing related subjects are either in general perspectives such as closed-loop supply chains (CLSC) research [9,97], reverse logistics [33,86], or in operational perspectives such as production planning and control ( [40,65]; Akcali and Cetinkaya 2011), [3] disassembly [56], scheduling [76], aftermarket strategy [88], and design for remanufacturing [47]. With the increasing importance and academic interest, this paper conducts a literature review of the quantitative modeling research in Core Acquisition Management, with the aim to summarize the recent research development and outline possible further research in Core Acquisition Management.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature review studies in remanufacturing related subjects are either in general perspectives such as closed-loop supply chains (CLSC) research [9,97], reverse logistics [33,86], or in operational perspectives such as production planning and control ( [40,65]; Akcali and Cetinkaya 2011), [3] disassembly [56], scheduling [76], aftermarket strategy [88], and design for remanufacturing [47]. With the increasing importance and academic interest, this paper conducts a literature review of the quantitative modeling research in Core Acquisition Management, with the aim to summarize the recent research development and outline possible further research in Core Acquisition Management.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 76 journal articles on the remanufacturing processes was reported by Lage and Godinho-Filho [11]. Morgan and Gagnon [12] organized and reviewed journals up to 2011 with the intention of gathering a progression timeline of remanufacturing. The impact of two-product joint life cycles on the capacity planning of remanufacturing networks was presented by Georgiadis and Athanasiou [13].…”
Section: Environmentally Conscious Manufacturing and End-of-life Prodmentioning
confidence: 99%
“…In this case, the first failure is given by Equation (5) and subsequent failures are given by Equation (11). The expected number of failures in [0, W 1 ) is given by Equation (12).…”
Section: Analysis Of Frw-prw Combination Policymentioning
confidence: 99%
“…Kim et al [14] defined the basic disassembly scheduling problem and presented a literature review of existing studies on disassembly scheduling. Morgan and Gagnon [15] published a detailed review paper about disassembly and remanufacturing scheduling.…”
Section: Disassemblymentioning
confidence: 99%